It Takes Two to Tango: Including a Female Perspective in Reproductive Biology. (23rd July 2020) - Orr, Teri J; Burns, Mercedes; Hawkes, Kristen; Holekamp, Kay E; Hook, Kristin A; Josefson, Chloe C; Kimmitt, Abigail A; Lewis, A Kelsey; Lipshutz, Sara E; Lynch, Kathleen S; Sirot, Laura K; Stadtmauer, Daniel J; et al.
Synopsis: Like many scientific disciplines, the field of reproductive biology is subject to biases in terminology and research foci. For example, females are often described as coy and passive players in reproductive behaviors and are termed "promiscuous" if they engage in extra-pair copulations. Males on the other hand are viewed as actively holding territories and fighting with other males. Males are termed "multiply mating" if they mate with multiple females. Similarly, textbooks often illustrate meiosis as it occurs in males but not females. This edition of Integrative and Comparative Biology (ICB) includes a series of papers that focus on reproduction from the female perspective. These papers represent a subset of the work presented in our symposium and complementary sessions on female reproductive biology. In this round table discussion, we use a question and answer format to leverage the diverse perspectives and voices involved with the symposium in an exploration of theoretical, cultural, pedagogical, and scientific issues related to the study of female biology. We hope this dialog will provide a stepping-stone toward moving reproductive science and teaching to a more inclusive and objective framework.